Relationship between group work competencies and satisfaction with project-based learning among university students - Melguizo-Garín, Ana Isabel; Ruiz-Rodríguez, Iván de los Reyes; Peláez-Fernández, María Ángeles; Salas-Rodríguez, Javier; Serrano-Ibáñez, Elena Rocío (Frontiers in Psychology, 2022)
There is a growing interest in improving the teaching–learning process at all levels of education, including higher education. In recent years, university institutions have been taking action to renew and modernize the way in which they teach and learn, making the process more dynamic and closer to the current social reality. Competencies such as the ability to work in a team have become essential for the successful implementation of innovative methodologies in which student participation is particularly relevant. Student acceptance is key to the success of any teaching methodology; however, the influence of group work skills on satisfaction with innovative methodologies such as project-based learning (PBL) has not yet been tested among university students. Thus, the objective of this study is to explore the association between group work competencies and satisfaction with PBL. A total sample of 359 students from two Spanish universities participated in the research. Our results reveal that there is a significant and positive relationship between competencies related to group work and satisfaction with PBL. In addition, a multiple regression analysis shows that the competencies “Conception of group work,” “Usefulness of group work,” “Planning of group work by teachers,” and “Group norms” increase satisfaction with the use of the PBL methodology. This work expands our knowledge about the role in increasing students’ satisfaction that is played by the ability of college students to work as a team. These findings could also guide teachers interested in new teaching methodologies.
Este estudio, realizado en dos universidades españolas, examina cómo las competencias de trabajo en grupo influyen en la satisfacción de los estudiantes universitarios con el aprendizaje basado en proyectos (ABP). Participaron 359 estudiantes de diversas carreras, evaluando competencias como la concepción del trabajo en grupo, su utilidad, la planificación por parte de los profesores y las normas de grupo. Los hallazgos revelan una relación positiva significativa entre estas competencias y la satisfacción con el ABP. Específicamente, aspectos como la percepción del trabajo en grupo, su utilidad percibida y la planificación y apoyo del profesorado mostraron ser predictores clave de la satisfacción. Estos resultados subrayan la importancia de las habilidades de colaboración y la organización efectiva en el ABP, resaltando la relevancia de un rol activo del profesorado en la planificación y apoyo del trabajo grupal. El estudio destaca que la satisfacción con el ABP no solo depende de las metodologías empleadas sino también de cómo los estudiantes perciben y participan en el trabajo en grupo. Esta investigación aporta evidencia significativa sobre el papel de las competencias de trabajo en grupo en la educación superior, sugiriendo que la mejora de estas habilidades podría ser una estrategia valiosa para aumentar la satisfacción de los estudiantes con metodologías participativas como el ABP. Además, los resultados podrían guiar a los docentes en la implementación de metodologías innovadoras, resaltando la necesidad de centrarse en las habilidades grupales y sociales de los estudiantes. El estudio también sugiere futuras investigaciones para explorar otros factores individuales y contextuales que influyen en la satisfacción con el ABP, como el rendimiento académico, el tamaño de la clase o la disposición del espacio. Este enfoque integral tiene el potencial de enriquecer la experiencia educativa de los estudiantes y mejorar la calidad de la enseñanza en la educación superior.
Keywords: Enseñanza en grupo; Group work; Competencies; Project-based learning; Higher education; Satisfaction